2008
DOI: 10.1177/0891988708320971
|View full text |Cite
|
Sign up to set email alerts
|

Depression, Disability and Intermediate Pathways: A Review of Longitudinal Studies in Elders

Abstract: Cross-sectional studies demonstrate depression is associated with disability in elders. These studies also report that disability in depressed elders is associated with greater medical illness burden, cognitive impairment, and behavioral changes. Only longitudinal studies, however, can determine the impact of depression and its comorbidities on functional decline. This review summarizes the findings of 20 longitudinal studies examining the relationship between baseline or incident depression and functional dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1
10

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 83 publications
8
54
1
10
Order By: Relevance
“…Vascular comorbidity is of particular importance in this context as it has been reported to be associated with functional decline (Wang et al, 2002). Depression could be an intermediate state between cerebral vascular disease and disability (Alexopoulos et al, 1997;Schillerstrom et al, 2008). We however, controlled for hypertension, diabetes, stroke, and cardiovascular disease and the association remained significant, suggesting that this pathway does not fully explain the association.…”
Section: Mechanisms Potentially Involved In the Association Between Dcontrasting
confidence: 41%
See 2 more Smart Citations
“…Vascular comorbidity is of particular importance in this context as it has been reported to be associated with functional decline (Wang et al, 2002). Depression could be an intermediate state between cerebral vascular disease and disability (Alexopoulos et al, 1997;Schillerstrom et al, 2008). We however, controlled for hypertension, diabetes, stroke, and cardiovascular disease and the association remained significant, suggesting that this pathway does not fully explain the association.…”
Section: Mechanisms Potentially Involved In the Association Between Dcontrasting
confidence: 41%
“…Indeed in the same cohort, an increase in depression-related 4-year mortality risk was observed in men with mild (OR=2.8) and treated severe DS (OR=5.3) whereas in women only non-treated severe DS which slightly increased risk (OR=1.8) (Ryan et al, 2008). Several previous studies have reported an increase in activity limitations (most frequently severe ADL limitations) associated with DS in elderly community cohorts (see (Carriere et al, 2009;Schillerstrom et al, 2008), for reviews). Only two prospective studies have examined the impact of gender differences on severe level of disability (Barry et al, 2009;Dalle Carbonare et al, 2009).…”
Section: Gender Differences In Depression-related Activity Limitationmentioning
confidence: 83%
See 1 more Smart Citation
“…While the association between depression and onset of disability in the elderly has been extensively explored (Carriere et al, 2009;Schillerstrom et al, 2008) with depression being confirmed as an independent risk factor even when multiple confounding effects are taken into account (Carriere et al, 2011), less is known about the association between anxiety and disability even though the prevalence of anxiety disorder in the elderly appears to be as high and maybe even higher than that of depression. In the present sample, 2.3% of subjects aged 65 and above had a baseline major depressive episode and 13.2% were classified as having severe depressive symptoms, whereas 14.2% had at least one baseline anxiety disorder; there was a three-fold increase in the prevalence of MDE (6.7%) among subjects with at least one anxiety disorder.…”
Section: Anxiety In the Elderlymentioning
confidence: 99%
“…While depression has been consistently demonstrated to be an independent risk factor for functional loss in the elderly (Carriere et al, 2011;Carriere et al, 2009;Schillerstrom et al, 2008), little is currently known about the association between anxiety disorders and activity limitations: previous research being largely based on cross-sectional observations (Brenes et al, 2008;Cairney et al, 2008;de Beurs et al, 1999;Porensky et al, 2009;Sareen et al, 2006). To date only two prospective studies have been undertaken.…”
Section: Introductionmentioning
confidence: 99%